(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article examines the impact of free trade agreements (FTAs) on the economic development of the participating countries. The article analyzes how such agreements contribute to improving trade flows, GDP growth, attracting foreign investment and developing individual sectors of the economy. Attention is paid to possible negative consequences, such as increased inequality and vulnerability of local producers. The study is based on data from international organizations and statistical data. The results show that the success of FTAs largely depends on countries’ level of training, institutional support, and policy coherence.